(untitled) (Alberta Journal of Educational Research, 2015)
Debates have been taking place in higher education communities in Canada and other Anglo-American contexts between defenders of liberal education and promoters of neoliberalism. One development not addressed is the growth of co-operative education (co-op). The origins of co-op may reside in John Dewey’s (1939, 1966) ideas about experience and democracy, but co-op also resembles a neoliberal phenomenon. We reviewed the North American literature on co-op from 1990-2014 to see if and how the rise of co-op has posed a challenge to liberal education. Our analysis revealed a dominant focus on instrumental and economic purposes reflecting neoliberal reforms, strands of philosophical and empirical inquiry consistent with liberal education, and a notable absence of critical, emancipatory outlooks. We contend that co-op researchers need to rediscover the socially progressive promise of experiential education, informed by other educational subfields. We also argue that researchers interested in neoliberal challenges to liberal education need to tap co-op as a site of inquiry. Des débats ont lieu dans des communautés de l’enseignement supérieur au Canada et dans des contextes anglo-américains, entre les apôtres d’une éducation libérale et les promoteurs du néolibéralisme. Un élément qui n’est pas abordé est la croissance de l’éducation coopérative. Les origines de l’éducation coopérative pourraient se trouver dans les idées de John Dewey (1939, 1966) touchant l’expérience et la démocratie, mais celle-ci ressemble également à un phénomène néolibéral. Nous avons examiné la documentation nord-américaine portant sur l’éducation coopérative de 1990 à 2014 pour déterminer dans quelle mesure la montée de l’éducation coopérative pose un problème à l’éducation libérale. Notre analyse a révélé un fort accent sur des objectifs instrumentaux et économiques reflétant des réformes néolibérales, des éléments d’enquête philosophique et empirique compatibles avec une éducation libérale, et une absence notable de perspectives critiques et émancipatrices. Nous soutenons que les chercheurs en l’éducation coopérative doivent redécouvrir la promesse progressiste sur le plan social qu’est celle de l’éducation expérientielle éclairée par d’autres sous-zones éducatives. Nous attestons également que les chercheurs qui s’intéressent aux défis néolibéraux à l’éducation libérale doivent se pencher sur l’éducation coopérative.